Tuning Spin-Orbit Torques Across the Phase Transition in VO2/NiFe Heterostructure - Kim, Jun-young; Cramer, Joel; Lee, Kyujoon; Han, Dong-Soo; Go, Dongwook; Salev, Pavel; Lapa, Pavel N.; Vargas, Nicolas M.; Schuller, Ivan K.; Mokrousov, Yuriy; Jakob, Gerhard; Klaeui, Mathias (John Wiley & Sons Ltd., 2022)
The emergence of spin-orbit torques as a promising approach to energy-efficient magnetic switching has generated large interest in material systems with easily and fully tunable spin-orbit torques. Here, current-induced spin-orbit torques in VO2/NiFe heterostructures are investigated using spin-torque ferromagnetic resonance, where the VO2 layer undergoes a prominent insulator-metal transition. A roughly twofold increase in the Gilbert damping parameter, alpha, with temperature is attributed to the change in the VO2/NiFe interface spin absorption across the VO2 phase transition. More remarkably, a large modulation (+/- 100%) and a sign change of the current-induced spin-orbit torque across the VO2 phase transition suggest two competing spin-orbit torque generating mechanisms. The bulk spin Hall effect in metallic VO2, corroborated by the first-principles calculation of the spin Hall conductivity sigma SH approximate to-104PLANCK CONSTANT OVER TWO PIe omega-1 m-1, is verified as the main source of the spin-orbit torque in the metallic phase. The self-induced/anomalous torque in NiFe, with opposite sign and a similar magnitude to the bulk spin Hall effect in metallic VO2, can be the other competing mechanism that dominates as temperature decreases. For applications, the strong tunability of the torque strength and direction opens a new route to tailor spin-orbit torques of materials that undergo phase transitions for new device functionalities.